Islamic Law and Gender: a Misconception of Roles and Responsibilities in Parenting - Pitrotussaadah, Pitrotussaadah; Fadhilah, Eva; Zulfikar, Faisal (De Jure: Jurnal Hukum dan Syari'ah, 2023)
Parenting roles and responsibilities are often influenced by gender stereotypes that exist in society. There are different expectations and demands on the roles of men and women in parenting. For instance, women (mothers) are often considered primarily responsible for caring for and educating children, while men (fathers) are considered more as breadwinners and leaders of the family. Additionally, it is frequently questioned when a father bears a child while away from the child's mother. This study seeks to evaluate and examine the notion of roles and responsibilities in parenting from the perspective of gender equality and Islamic law, employing a library research method (descriptive analysis research) that involves objectively assessing and describing occurrences. According to the findings of the study, parenting plays a significant role in the personality development and formation of children. According to a gender perspective, both mothers and fathers have the same role in raising children. According to the perspective of Islamic law, parenting is based on religious teachings which provide guidelines on how to educate children in an Islamic way. Parents are expected to carry out parenting responsibilities by taking into account Islamic values, including respecting children's rights under religious teachings. Keywords: parenting; Islamic law; gender.